Seasonal optimization of envelope and shading devices oriented towards low-carbon emission for premodern historic residential buildings of China - Shiya Zhao; Jianxin Diao; Sheng Yao; Jingyu Yuan; Xuan Liu; Min Li (Case Studies in Thermal Engineering)
The renovation of historic residential buildings is required to balance the daylighting and thermal comfort of the building space with the conservation of the architectural features. However, there is a lack of dynamic optimization in the dimension of seasons for the historic residential buildings, while conservation factors are not considered in the design strategies. Therefore, in this study, a seasonal multi-optimization method for the historic residential buildings was introduced to improve the daylighting and thermal comfort while reducing carbon emissions. At first, the field and network investigation were conducted and a prototypical model was developed based on the second-order cluster analysis method. Furthermore, the envelope (internal insulation materials, internal insulation thickness, window types) and shading devices (inclination angle of shutters and shutter depth for different seasons and orientations) were optimized based on the Grasshopper platform. Finally, the best renovation solution orientated by low-carbon emission was proposed. The results show that the optimal material for the internal insulation of the wall is polyurethane, which has a thickness of 0.10 m. The window type is 6 mm high transmission reflective glass. The greatest inclination angle of shutters in summer is the window facing southeast. Conversely, in spring and autumn, the southwest windows have the greatest inclination angle of shutters. In winter, the inclination angle of shutters for the northeast windows is a maximum of 26°. The inclination angle of shutters for southwest windows in autumn is the most needed for design, and the angle is upward reversed 47°. The maximum shutter depth of 0.19 m in the southeastern windows is a 72.71 % improvement relative to the minimum shutter depth. Compared with the prototypical model, the useful daylight illuminance of the building model is improved by 12.41 %, the thermal discomfort hours percentage is reduced 3.09 %, and the life cycle carbon emissions is reduced by 14.6 %. The optimal design strategies for the building envelope and shading devices considering conservation principles can improve the daylighting and thermal comfort of the historic residential buildings.